2019
DOI: 10.1093/jn/nxy286
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Serum Ferritin Concentration is Inversely Associated with Umbilical Cord Hemoglobin in Neonates Born to Adolescents Carrying Singletons and Women Carrying Multiples

Abstract: Background It has been proposed that the fetus prioritizes iron for hemoglobin production over delivery to tissues. However, few studies have evaluated the interrelations between hemoglobin and multiple iron status biomarkers in umbilical cord blood. A full understanding is needed of how these parameters influence each other within cord blood to fully interpret iron and hematologic status at birth. Objectives We evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
1
16
1
Order By: Relevance
“…The study of Pateva et al [28] demonstrated that children of smoking mothers had significantly lower total iron levels compared with newborns of non-smokers, while Secovanic et al [25] observed increased levels of iron in the cord blood of smokers. In the current study, we observed significantly lower iron levels in children of smoking women; however, it was within the normal range for umbilical cord blood [29,30]. This may be due to the increased iron use for increased erythropoiesis in the blood of children of smoking mothers.…”
Section: Discussioncontrasting
confidence: 43%
“…The study of Pateva et al [28] demonstrated that children of smoking mothers had significantly lower total iron levels compared with newborns of non-smokers, while Secovanic et al [25] observed increased levels of iron in the cord blood of smokers. In the current study, we observed significantly lower iron levels in children of smoking women; however, it was within the normal range for umbilical cord blood [29,30]. This may be due to the increased iron use for increased erythropoiesis in the blood of children of smoking mothers.…”
Section: Discussioncontrasting
confidence: 43%
“…The current study has raised the need to further investigate the relationship between ferritin and sTfR among infants and young children, and more studies are required to evaluate the association between cord ferritin and sTfR before using TBI estimates to evaluate iron status in the newborns. Delaney et al (9) have also questioned the application of current references ranges for use in neonates and how much they accurately reflect iron status.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-and intra-assay coefficients of variation were all below 5%. Total body iron (TBI) was calculated from the serum transferrin receptor/serum ferritin ratio as follows: TBI (mg/kg) = -[log(R/F ratio) -2.8229]/0.1207 (9).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, processes of neuronal development, synthesis of neurotransmitters, the myelin and glia cells production are affected. Alterations that occur in neurogenesis, mediated by the de cit of ferritin during embryonic and fetal life will determine permanent consequences on neurocognitive development from birth and throughout life (16) (17). Serum ferritin levels are directly related to iron deposits (18) (19).…”
Section: Discussionmentioning
confidence: 99%